2019
DOI: 10.1038/s12276-019-0220-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of Frizzled1 is associated with Wnt/β-catenin signaling inactivation in mesenchymal stem cells of patients with steroid-associated osteonecrosis

Abstract: The Wnt/β-catenin signaling pathway is associated with the pathogenesis of steroid-induced osteonecrosis. Our investigation studied whether aberrant CpG island hypermethylation of the FZD1 gene was present in patients with osteonecrosis of the femoral head (ONFH), which results in Wnt/β-catenin signaling inactivation and subsequent cell dysfunction. Bone marrow was collected from the proximal femurs of patients with steroid-associated ONFH ( n = 21) and patients with new femoral neck fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…focusing on the balance of osteogenesis, bone resorption and angiogenesis [28][29][30][31] . Among these mechanisms, the influenced osteogenic differentiation, proliferation and migration of MSCs are considered as the top factors leading to ONFH 8,9 . Glucocorticoid (GC)-treated models were used to study the mechanism of ONFH in vivo and in vitro, due to the use of GC as the common etiology of this disease 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…focusing on the balance of osteogenesis, bone resorption and angiogenesis [28][29][30][31] . Among these mechanisms, the influenced osteogenic differentiation, proliferation and migration of MSCs are considered as the top factors leading to ONFH 8,9 . Glucocorticoid (GC)-treated models were used to study the mechanism of ONFH in vivo and in vitro, due to the use of GC as the common etiology of this disease 32 .…”
Section: Discussionmentioning
confidence: 99%
“…MSCs with pluripotency of differentiation play a critical role in ONFH 7,8 . The impaired osteogenic differentiation and migration of MSCs is considered as the major factor leading to ONFH 9 . However, MSCs implantation remains a high rate of failure 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Many diseases, including osteoporosis and osteonecrosis, have been shown to be significantly associated with imbalances between osteogenic and adipogenic differentiation of BMSCs [44, 45]. Recent studies also revealed that ONFH is mainly caused by increased differentiation of BMSCs into adipocytes and decreased bone osteogenesis [46, 47]. This study showed increased adipogenesis and decreased osteogenesis in necrotic regions of the femoral head.…”
Section: Discussionmentioning
confidence: 64%
“…Gene function in osteogenesis RUNX2 Low TF, promote the expression of target genes and osteogenic differentiation (Zhang R. P. et al, 2011;Wakitani et al, 2017) OSX Low TF, promote the expression of target genes and osteogenic differentiation (Zhang R. P. et al, 2011;Farshdousti Hagh et al, 2015) BMP2 Low Bone growth factor, promote osteogenic differentiation (Fu et al, 2013;Raje and Ashma, 2019) SOST High Glycoprotein, inhibit osteogenic differentiation (Reppe et al, 2015a;Cao et al, 2019) ALP Low Hydrolyze phosphate ester to provide necessary phosphoric acid for the deposition of hydroxyapatite, and at the same time hydrolyze pyrophosphate to remove its inhibitory effect on bone salt formation (Delgado-Calle et al, 2011;Yang and Duan, 2016;Licini et al, 2019) OCN Low Maintain normal bone mineralization (Villagra et al, 2002;Licini et al, 2019) Frizzled1 Low Activate the wnt pathway and promote osteogenic differentiation (Wu et al, 2019) RANKL High Stimulate osteoclast differentiation and promote bone resorption (Ghayor and Weber, 2016;Behera et al, 2018) OPG Low Inhibit osteoclast differentiation (Ghayor and Weber, 2016;Wang et al, 2018) LOX Low Promote osteogenic differentiation (Thaler et al, 2011) ESR1 Low Promote osteogenic differentiation (Penolazzi et al, 2004) DLX5 Low Promote osteogenic differentiation Li et al, 2009) Alu elements…”
Section: Genes Methylation Level During Osteogenic Differentiationmentioning
confidence: 99%